SEMI-AUTOMATED COMPUTATIONAL METHOD FOR SKELETAL MUSCLE FIBER TYPING WITH LECTINS: CORRELATION WITH MORPHOMETRIC STUDIES (Iraqi Journal of Medical Sciences, 2016)
Background :Muscle fiber typing has been an extensive field of study for many years. Though, limited researches applied lectin histochemistry in the clinical diagnosis of muscle disorders; attention was directed mainly towards enzyme histochemistry.Objective:The use of lectins as recognition systems based on specific protein-carbohydrate interactions in correlation with muscle fibers morphometric standards and optical density features to favor the diagnostic procedures of muscle disorders.Methods:Cross-sections of tibialis anterior muscle from 15 adult rats were stained with Con A, PNA, SBA, WGA, SWGA, LFA, UEA-I, and UEA-II lectins. Photographs of stained sections were analyzed with ImageJ 1.44 software for muscle fiber area, perimeter, optical density, and integrated density.Results:There were statistically significant differences between the parameters of muscle fiber types under study (P
Keywords: Lectins; Muscle fiber typing; Quantitative; Optical density; Morphometry